2007
DOI: 10.1200/jco.2006.08.5829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Subset of Myeloid Suppressor Cells in Peripheral Blood of Melanoma Patients With Modulation by a Granulocyte-Macrophage Colony-Stimulation Factor–Based Antitumor Vaccine

Abstract: CD14+HLA-DR-/lo cells exerting TGF-beta-mediated immune suppression represent a new subset of MSC potentially expandable by the administration of GM-CSF-based vaccines in metastatic melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
506
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(537 citation statements)
references
References 33 publications
25
506
5
1
Order By: Relevance
“…However, accumulating studies show that these factors also promote the expansion of myeloid suppressive components, with undesirable consequences on tumor antigen-specific immune responses [182]. For instance, GM-CSF-based anti-tumor vaccine to human metastatic melanoma patients induced a subset of immunosuppressive MDSCs that involved TGFβ secretion [183]. GM-CSF may increase immune responses when administered at low doses, while causing an opposite effect at high doses [182].…”
Section: Regulation Of Neutrophil Mobilization Recruitment and Activmentioning
confidence: 99%
“…However, accumulating studies show that these factors also promote the expansion of myeloid suppressive components, with undesirable consequences on tumor antigen-specific immune responses [182]. For instance, GM-CSF-based anti-tumor vaccine to human metastatic melanoma patients induced a subset of immunosuppressive MDSCs that involved TGFβ secretion [183]. GM-CSF may increase immune responses when administered at low doses, while causing an opposite effect at high doses [182].…”
Section: Regulation Of Neutrophil Mobilization Recruitment and Activmentioning
confidence: 99%
“…In cancer patients, the number of circulating MDSCs significantly increases compared to healthy subjects 38 . Our study, however, is the first demonstration in a cancer model that TLR stimulation leads to local MDSCs expansion, accounting for enhanced tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that stimulation of TLR7 expressed by adenocarcinoma cells modulated the immune infiltrate, leading to a significant expansion in MDSCs, associated with an increased secretion of CCL2 and GM-CSF in the tumor microenvironment. Both these cytokines are known to play a key role in the recruitment of MDSCs 38,41,42 . Indeed, the absence of CCL2 production by cancer cells considerably reduces the recruitment of MDSCs into tumors 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma patients, another subset of monocytic MDSC has been identified with CD14 + CD11b + HLA-DRl ow/neg phenotype [109,110]. Two main subpopulations of MDSCs taking part in suppression of immune system in melanoma and colon cancer are: CD14 + monocytes and CD15 + neutrophils and both of these cell types express IL-4 receptor (CD124).…”
Section: Myeloid-derived Suppressor Cells In Tumor Environmentmentioning
confidence: 99%